A utilização dos laboratórios escolares em instituições de ensino na cidade de Uberaba - GONÇALVES FILHO, Roberto Salgado (2018)
This research aimed to evaluate the laboratories of public and private educational institutions in Middle School in the urban area of Uberaba City. This evaluation involved quantifying the laboratories in schools and verifying their use. In total 68 schools were visited. The research was carried out by the fact that laboratories play an important role in the teaching-learning process by allowing the student to research, test hypotheses, construct projects and conduct experiments in practice and often the laboratory is not even used. In addition, we analyzed the existence of practical classes and their influence on student performance and, finally, the author’s contribution with the elaboration of a script model of how to carry out a practical lesson. In order to obtain the results, a methodology was used as a quantitative research in the form of a survey for the directors and teachers of the schools, thus obtaining the graphs with all the data necessary to develop the results. The influence of the practical classes on students performance was obtained through the analysis of the graphs generated by the answer in the questionnaires that helped to infer results in the development of the student. The elaboration of a script model of how to perform a practical lesson is obtained through the author's experience since the project, because it is his area of professional activity and also based on the cognitive theories of teaching-learning as constructivism and constructionism discussed in the present work. It was found that laboratories are important, as well as practical classes. It was found that although there are laboratories of practical classes in the schools of Uberaba, their use is still precarious, with little incentive or even not giving due importance to this aspect. Traditionalist teaching still prevails, and the student is merely a passive subject in the process of knowledge construction.